Localisation as Sociocultural Adaptation of Modern Design of Visual Communications - Natalya Udris-Borodavko; Vadym Abyzov (Культура і мистецтво у сучасному світі, 2024)
The aim of the article is to ground and formulate the definition of the term “localisation” in design using the example of visual communications. Results. A review of definitions and interpretations of localisation in different scientific and industrial spheres highlights that the term has different semantic meanings. In the sphere of visual communications, the concept appeared in web design, programming interfaces of programmes and games in the context of language, as well as technical, normative (State Standards) and legal parameters. Nowadays, the use of the term has expanded to the majority of graphic design, branding and marketing product. Its content is associated with sociocultural characteristics of the target groups. Interviews conducted with experts in the re-publishing and redesign of English-language books in the Ukrainian language, advertising communications, curatorship in mural placement and social poster display confirm the relevance of the content and design adчaptation to the specifics of target groups. Localisation in design is defined as a strategy in increasing the functional and communicative efficiency of the project through the adaptation of the content and design to the specifics of sociocultural, legislative, technological, geographical and historical conditions of its use within the country, region, etc. Scientific novelty. For the first time in the theory of design, the term “localisation” is grounded and introduced (using the example of visual communications); the specifics of using the concept of “local” in the context of consideration of these phenomena are clarified; the results of interviews of Ukrainian experts with experience in the localisation of visual communications are presented; the necessity in sociocultural adaptation of the content and design of visual communications to the requests of target groups is emphasised. Conclusions. In conditions of globalisation, the significance of localisation of visual communication projects is increasing. Its implementation requires immersion in the local culture and/or close contact with their representatives during the design process. However, the most effective localisation can be carried out directly by a representative of the target group as a carrier of its local culture.